Vapor-phase Hydrosilylation Using a Transition Metal Complex Catalyst in a Liquid Polymer Medium Supported on Silica Gel - Okamoto, Masaki; Kiya, Hironari; Matsumura, Akihiko; Suzuki, Eiichi (Catalysis letters, 2008)
Transition metal catalysts in various liquid polymer media supported on silica gel were prepared and used for vapor-phase hydrosilylation. Tetraammineplatinum(II) chloride and potassium hexachloroplatinate(IV) in a polyethylene glycol (PEG) medium showed high and stable activity. Deactivation of the catalyst was not observed unless a high platinum concentration in PEG was used. When the amount of PEG was 40 vol% of the pore volume of silica gel, PEG was coated on the pore walls of the silica gel, and did not block the pore openings. Active species in the PEG were formed only during the reaction.